I LOVE INDONESIA: EFL LEARNERS’ PERCEPTIONS ON WEB-FACILITATED LANGUAGE LEARNING - Muzakki Bashori (EduLite: Journal of English Education, Literature and Culture, 2017)
The integration of computer in the service of FL (Foreign Language) learning is expected to be inevitable in the future. It is seemingly due to (a) its considerable affordances for EFL (English as a Foreign Language) learners, (b) the characteristics of today’s learners as the Generation Z (González-Lloret & Ortega, 2014), and (c) the widespread use of the internet in the 21st century. This situation then leads to transforming CALL (Computer-Assisted Language Learning) into WFLL (Web-Facilitated Language Learning) as an alternative paradigm for EFL teachers and learners. Furthermore, TBLT (Task-Based Language Teaching) is likely to serve as a pedagogical framework in designing the Web for the purpose of FL learning. The present study was therefore mainly aimed at (a) developing a particularly teacher-designed learning website, namely I Love Indonesia, and (b) investigating high school learners of English in Indonesia with different attitudes towards CALL (positive/moderate/negative) in correlation with how they perceive WFLL (agree/disagree) and perform web-based activities. Descriptive Statistics, IF Function in Excel, Correlation Analysis, and Independent-samples t-test were employed in the study. Finally, the findings of the study showed that (a) the website seems to benefit EFL learners in some certain aspects, and (b) positive attitude learners are likely to perceive more positively (agree) than moderate and negative attitude learners (disagree) on the use of the website for the purpose of language learning. A greater number of learners over a longer period of time should be taken into account when conducting further studies on the effectiveness of the website for EFL learners in order to be able to shed some light on learners’ language development. Keyword: attitude, perception, task-based language teaching, web-facilitated language learning